2018
DOI: 10.1177/0961203318759607
|View full text |Cite
|
Sign up to set email alerts
|

The lupus patient with positive rheumatoid factor

Abstract: Background Patients with systemic lupus erythematosus (SLE) may form clusters with clinical manifestations and autoantibodies. Objective The objective of this report is to study whether SLE patients with positive rheumatoid factor (RF) have a special clinical and/or serological profile. Methods A retrospective study of 467 SLE patients seen at a single rheumatology unit was conducted. Epidemiological data (age, gender, age at disease onset, ethnic background and tobacco use), clinical data (malar rash, photose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…However, RF is not a specific antibody unique to RA. In lupus [14], Sjogren's syndrome [15], systemic sclerosis [16], and hepatitis C virus getrelated arthropathy (HCVrA) [17], these disease positive rates are not low as expected. A systematic review showed that the sensitivity of RF for early diagnosis was from 77 to 80%, and the specificity was between 33 and 77% in 1987 diagnostic ACR criteria [18].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 84%
“…However, RF is not a specific antibody unique to RA. In lupus [14], Sjogren's syndrome [15], systemic sclerosis [16], and hepatitis C virus getrelated arthropathy (HCVrA) [17], these disease positive rates are not low as expected. A systematic review showed that the sensitivity of RF for early diagnosis was from 77 to 80%, and the specificity was between 33 and 77% in 1987 diagnostic ACR criteria [18].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 84%
“…A variable proportion between 20–30% patients with adult-onset SLE are positive for rheumatoid factor and this correlated with clinical features of arthritis [ 185 , 186 ]. In contrast, a smaller proportion of adults with SLE have been found positive for anti-citrullinated cyclic peptides (CCP) antibodies, but this biomarker was associated with erosive arthritis in adults with SLE [ 187 ], in particular in SLE patients with higher titres [ 188 ].…”
Section: Arthritis Biomarkersmentioning
confidence: 99%
“…Clinical manifestation of SLE is heterogeneous and can affect multiple organs. Approximately 25% of SLE patients have RF ( 13 ), but these patients can also have anti-nuclear antibodies (ANA) and anti- double-stranded (ds) DNA antibodies.…”
Section: Introductionmentioning
confidence: 99%